Strategi Pemasaran Agroindustri Umkm Tenant Inkubator Agribisnis Universitas Riau - Muhammad Abror; Ahmad Rifai; Eliza ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this study was to analyze the marketing mix, identifying strengths, weaknesses, opportunities and threats in the marketing of pineapple chips, agroindustry marketing strategy agribusiness UMKM incubator tenants University of Riau. The method used in this research is a case study with a sample of 10 entrepreneurs. The results showed that the product consisted of pineapple chips of various sizes ranging from size 100 grams, 125 grams, 150 grams, 200 grams and bulk packaged in plastic containers and packaging boxes. The selling price of pineapple chips varies from Rp. 10,000 to Rp. 25.000 according to the packaging used. Distribution Marketing pineapple chips was focused on the local area that is Pekanbaru, Perawang, Danau Bingkuang but occasionally also carried into the field of marketing. Promotion done yet continuous pineapple chips businessmen, entrepreneurs simply do promotions with direct interaction to consumers, in addition to the promotion of the use of brochures and mass media do only a few businessmen, entrepreneurs also take advantage of the promotion through government assistance by following the bazaar and exhibitions. Marketing strategy pineapple chips to do is strengthen the brand or product brand, maximize product quality so as to penetrate the market, make loans to banks, in cooperation with other regional traders and standardized products. Keywords: Agroindustry, Marketing Mix, Marketing Strategies